Phase reversion mediated the dual heterogeneity of grain size and dislocation density in an equiatomic CrCoNi medium-entropy alloy - Kun Jiang; Jianguo Li; Xi Chen; Bin Gan; Qingbo Dou; Tao Suo (Journal of Materials Research and Technology)
An ultra-high strain rate (104 s−1) dynamic plastic deformation treatment at liquid nitrogen temperature (LNT-DPD) followed by annealing is carried out to obtain dual heterogeneity of grain size and dislocation density in an equiatomic CrCoNi medium entropy alloy (MEA). Such extreme loading conditions resulted in extensive phase transformation in this MEA. Subsequent annealing at 650 °C for 1 h further induced reverse phase transformation and partial recrystallization, forming a complex heterogeneous microstructure characterized by nested trimodal grain sizes and partitioned dislocation density. A superior yield strength of ∼800 MPa and a good ductility of ∼40% were simultaneously achieved in this heterogeneous alloy. In order to reveal the effects of grain size and dislocation density distributions on the mechanical property improvements, the underlying deformation mechanisms were systematically discussed. High density of geometrically necessary dislocations (GNDs) would be induced in complex heterogeneous structures during tensile deformation due to strain gradients or partitioning between different regions, which would lead to additional strengthening and work hardening. These results provide a novel approach to overcome the strength-ductility trade-off dilemma for FCC-structured MEAs.